2005
DOI: 10.1007/s10286-005-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of heart rate variability and blood pressure variability in individuals with spinal cord injury

Abstract: Individuals with spinal cord injury (SCI) are prone to orthostatic intolerance and an increased risk of cardiovascular disease. The use of heart rate variability (HRV) and blood pressure variability (BPV) as indices of cardiovascular regulation would be valuable in this population; however, their reproducibility has yet to be tested in those with SCI. The purpose of this study was to examine the day-to-day reproducibility of resting HRV and BPV in individuals with SCI. Ten individuals (age 35.9 +/- 13.2 yrs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
2
32
1
3
Order By: Relevance
“…Further, although the HF band did not significantly differ between the groups, a trend toward a reduction in this band in the P group was observed. As a result, this decrease in all frequency bands is reflected in a significant reduction in the total power of the spectrum, similar to the findings obtained by Uhlir et al 8 and Ditor et al 23 Regarding the nonlinear analysis, we obtained significant differences only in SD1 and SD2 but not in DFA1, DFA2 or sampen. DFA is a measure of roughness in the time series and predicts fatal cardiovascular events in various populations.…”
Section: Discussionsupporting
confidence: 91%
“…Further, although the HF band did not significantly differ between the groups, a trend toward a reduction in this band in the P group was observed. As a result, this decrease in all frequency bands is reflected in a significant reduction in the total power of the spectrum, similar to the findings obtained by Uhlir et al 8 and Ditor et al 23 Regarding the nonlinear analysis, we obtained significant differences only in SD1 and SD2 but not in DFA1, DFA2 or sampen. DFA is a measure of roughness in the time series and predicts fatal cardiovascular events in various populations.…”
Section: Discussionsupporting
confidence: 91%
“…These analyses are particularly useful, because they can be relatively simply performed, require only standard hospital equipment (electrocardiogram and beat-tobeat blood pressure), are noninvasive, and provide largely objective measures of autonomic control. These analyses are correlated with meaningful clinical measures of autonomic function and have been extensively validated in able-bodied individuals (13,46), with preliminary studies in SCI individuals confirming their use as reproducible indexes of autonomic cardiovascular regulation (13). Finally, the use of these measures may also be valuable in clinical trials evaluating changes in autonomic function over time or due to interventions aimed at improving autonomic function after SCI.…”
Section: Discussionmentioning
confidence: 88%
“…Although preliminary studies have shown that this technique is reproducible and reliable in SCI individuals (13), no study has correlated frequency domain indexes of autonomic tone with clinical measures of autonomic dysfunction after SCI. Furthermore, the evaluation of reflex delay using this technique has yet to be performed following SCI, despite the known link between increased baroreflex delay and other disorders of cardiac autonomic function (21,23).…”
mentioning
confidence: 99%
“…11 HRV measures in the frequency domain have been shown to be highly reproducible in adults with SCI and therefore represent a potentially valid measure of ANS dysregulation in this population. 13 Research employing HRV as a measure of ANS dysfunction in adults with SCI has found altered fluctuations in autonomic function in response to various activities such as tilt tests, exercise and digestion. 14,15 In comparison with AB controls, reduced sympathetic activity was found in adults with SCI, with no differences found for parasympathetic activity.…”
Section: Introductionmentioning
confidence: 99%